Pengaruh Penggunaan Media Powtoon Terhadap Peningkatan Hasil Menulis Teks Persuasi pada Siswa Kelas VIII SMP Islam Dampit Kabupaten Malang - Etty Umamy; Khoirul Efendiy; Hanum Lintang Siwi S; Zauharotul Zana Intan A (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
One of the functions of media in learning is to improve student learning outcomes. Therefore, the media plays a very important role. This research was conducted to determine the effect of using Powtoon media on improving the results of writing persuasive texts for class VIII Islamic Middle School students in Dampit, Malang district. The data in this study was obtained through pretest and posttest and analyzed statistically using computerized SPSS version 19.0 with regression analysis and hypothesis testing. Based on data analysis, a percentage number was obtained; Powtoon media coefficient, simple correlation coefficient, coefficient of determination, F significance respectively; 29.3%, 77.1%, 59.4%, and 40.6% which shows that Powtoon media has a significant influence on increasing the ability to write persuasive texts of students in class VIII of Dampit Islamic Middle School, Malang district, so it can be recommended as a media effective learning is related to students' writing skills and persuasive texts.